Deliberative Democracy in the 21st Century: Theories, Practices, and Global Perspectives - Pulanram, Phukanchanakrit (วารสารวิชาการสังคมศาสตร์สมัยใหม่ (Online), 2025)
This research explores the concept of deliberative democracy as a critical framework for navigating the complexities of political discourse in the 21st century. It highlights the transition from traditional democratic models that focus on electoral mechanisms to participatory approaches that prioritize reasoned debate and inclusive dialogue. Deliberative democracy encourages diverse viewpoints to be represented and reflected in public decision-making, thereby enhancing democratic legitimacy and citizen engagement. The study examines the influence of globalization, the rise of neoliberal ideologies, and the ethical challenges presented by contemporary geopolitical dynamics. It underscores how power asymmetries and strategic interests often undermine democratic values and moral responsibility, especially in global conflicts and environmental crises. Through a comparative analysis of theoretical perspectives and practical implementations across cultures, the research outlines how deliberative democracy can serve as a tool for conflict resolution, social cohesion, and sustainable development. Additionally, it considers how digital technologies and media influence public discourse and the formation of public opinion, offering both opportunities and risks for democratic engagement. The study advocates for a rethinking of democratic practices to include more participatory mechanisms that foster mutual understanding, civic responsibility, and long-term societal resilience. In doing so, it presents deliberative democracy as not only a political ideal but also a practical strategy for addressing global challenges and reinforcing democratic institutions in a rapidly changing world. By situating deliberative practices within current political and ethical debates, the research contributes to the ongoing discourse on the evolution of democratic governance in the face of emerging global realities.